Smoking in Correctional Settings Worldwide: Prevalence, Bans, and Interventions. (8th May 2018) - Spaulding, Anne C; Eldridge, Gloria D; Chico, Cynthia E; Morisseau, Nancy; Drobeniuc, Ana; Fils-Aime, Rebecca; Day, Carolyn; Hopkins, Robyn; Jin, Xingzhong; Chen, Junyu; Dolan, Kate A
Abstract: Smoking tobacco contributes to 11.5% of deaths worldwide and, in some countries, more hospitalizations than alcohol and drugs combined. Globally in 2015, 25% of men and 5% of women smoked. In the United States, a higher proportion of people in prison smoke than do community-dwelling individuals. To determine smoking prevalence in prisons worldwide, we systematically reviewed the literature using Preferred Reporting Items for Systematic Reviews and Meta-Analyses guidelines; we also examined whether prisons banned smoking or treated smokers. We searched databases for articles published between 2012 and 2016 and located 85 relevant articles with data representing 73.5% of all incarcerated persons from 50 countries. In 35 of 36 nations (97%) with published prevalence data, smoking for the incarcerated exceeded community rates 1.04- to 62.6-fold. Taking a conservative estimate of a 2-fold increase, we estimated that, globally, 14.5 million male and 26, 000 female smokers pass through prisons annually. Prison authorities' responses include permitting, prohibiting, or treating tobacco use. Bans may temporarily improve health and reduce in-prison health care costs but have negligible effect after prison release. Evidence-based interventions for smoking cessation effective outside prisons are effective inside; effects persist after release. Because smoking prevalence is heightened in prisons, offering evidence-based interventions to nearly 15 million smokers passing through yearly would improve global health.